Circumpolar Biodiversity Monitoring Programme: Coastal Biodiversity Monitoring: Background Paper. - D., McLennan; R. Anderson; S. Wegeberg; M. Pettersvik Arvnes; L. Sergienko; C. Behe; P. Moss-Davies; S. Fritz; C. Markon; T. Christensen; T. Barry; C. Price (CAFF International Secretariat, 2016)
The primary goal of the CEMG is to develop a long term, integrated, multi-disciplinary, circumpolar Arctic Coastal Biodiversity Monitoring Plan (the Coastal Plan) that relies on science and Traditional Knowledge, and has direct and relevant application for communities, industry, government decision makers, and other users. In addition to the monitoring plan, the CAFF working group has asked the CBMP, and thus the CEMG, to develop an implementation plan that identifies timeline, costs, organizational structure and partners. This background paper provides a platform for the guidance for the development of the Coastal Plan and is produced by the CEMG with assistance from a number of experts in multiple countries.